When elites polarize over polarization: Framing the polarization debate in Turkey. (21st November 2018) - Aydın-Düzgit, Senem; Balta, Evren
Abstract: This article aims to explore the views of the Turkish elite on the state of polarization in Turkey. By identifying four political frames—namely, harmony, continuity/decline, conspiracy, and conflict—that selected Turkish political and civil society elites use in discussing the phenomenon of polarization in the country through their contributions to a workshop and in-depth qualitative interviews, the article finds that there is a considerable degree of polarization among the Turkish elite regarding their views on the presence of polarization in Turkey. Moreover, this overlaps with the divide between the government and the opposition in the country. An analysis of the justificatory arguments employed in constituting the aforementioned frames shows that, while those elites who deny the existence of polarization seek its absence in essentialist characteristics of society, in reductionist comparisons with history, or in internal/external enemies, those who acknowledge polarization's presence look for its roots in political and institutional factors and processes. The article highlights how, given the denial of polarization by the pro-government elite and the substantial gap between the two camps' justificatory narratives, the currently reported high rates of polarization in Turkey can, at best, be expected to remain as is in the near future, barring a radical change in political constellations.